Infrastructure as Code Development in Cloud Computing Using Terraform for The Ministry of PUPR Application - Firmansyah Wicaksono; Angga Setiyadi (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
Terraform, as one of the Infrastructure as Code (IaC) tools, simplifies consistent and efficient cloud resource development using HashiCorp Configuration Language (HCL), a declarative syntax where each code block defines the resources to be provisioned. This study aims to build Google Cloud Platform services using Terraform and develop a simple web application related to the Ministry of PUPR with CRUD (Create, Read, Update, Delete) functionality, tested and monitored using the DevOps software development method. Docker is utilized as a container platform to package applications, ensuring consistent management from development to production. Additionally, CI/CD (Continuous Integration / Continuous Delivery / Deployment) pipelines are integrated to automate development processes, accelerating application deployment alongside cloud services built with Terraform. The results show that combining Terraform, CI/CD pipelines, and Docker within the Google Cloud Platform ecosystem using DevOps increases efficiency, effectiveness, speed, and consistency in managing cloud infrastructure and application deployment processes